Protein enrichment of the coproduct of sisal defibration using yeast and filamentous fungi (Research, Society and Development, 2025)
Sisal (Agave sisalana Perrine) is a plant from the Asparagaceae family that has become a valuable source of income for numerous families in the state of Bahia. Its cultivation is mainly intended for the creation of artisanal products, which stimulate the local economy. However, its processing generates waste materials that often lack a defined use but can be repurposed as animal feed. In this context, the present study aimed to evaluate the increase in protein content of the sisal coproduct following semi-solid fermentation over periods of 8, 24, 32, and 48 hours, using the fungi Lentinus tigrinus, Trametes villosa, and the yeast Saccharomyces cerevisiae. A significant variation in crude protein (CP) levels was identified for each microorganism applied (p